2021
DOI: 10.2991/assehr.k.210326.053
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Smartphone Based Learning Media to Improve Students’ Critical Thinking Skills During Covid-19 Pandemic

Abstract: This research aims to determine the effect of smartphone-based learning media in the students' critical thinking skills. This research was a quasi-experimental with only Posttest Control Group Design. The sample of this reasearch were students of class XI MIPA 1 and XI MIPA 2 at SMAN 1 Ngaglik in the academic year 2019/2020 who were taken by simple random sampling. Data collection instrument was developed based on indicators critical thinking skills namely understanding, application, analysis, evaluation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this study, the learning objective is to be skilled at completing tasks. The use of learning media that facilitates students during the COVID-19 pandemic helps students become experienced in completing the tasks given [24]- [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the learning objective is to be skilled at completing tasks. The use of learning media that facilitates students during the COVID-19 pandemic helps students become experienced in completing the tasks given [24]- [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sa'diyah et al, [12] conducted a study exploring smartphone-based learning to enhance critical thinking skills. They used four indicators: understanding, application, analysis, evaluation, and generalizing.…”
Section: Methodology 21 Literature Review: Smartphone For Educationmentioning
confidence: 99%
“…Although currently the COVID-19 condition has improved and learning activities have started to be conducted onsite in face-to-face mode, best practices from online learning can still be used to enhance and support the effectiveness of learning. For example: Sa'diyah et al, [12] found that the experimental class that applied smartphone-supported learning had significantly higher critical thinking skills than the control class.…”
Section: Introductionmentioning
confidence: 99%
“…The cultural context of Indonesian society is presented through the delivery of educational technology [306,[313][314][315][316][317][318][319]. The former interdisciplinary aspect of physics education and the demands of 21st century learning drives an intention during the design and implementation of educational technology on physics [304,320,321].…”
Section: Topic 7: Educational Technologymentioning
confidence: 99%